Modelling monthly diffuse solar radiation fraction and its validity over the Indian sub‐tropics. (21st November 2011) - Singh, Jyotsna; Bhattacharya, Bimal K.; Kumar, Manoj; Mallick, Kaniska
Abstract A three‐parameter sigmoidal 'local' model (climate‐specific) and a 'regional' model (common for all climates) have been developed for measuring the monthly average diffuse solar radiation fraction from atmospheric transmissivity by using large, 21‐year datasets (1973–1993) over four stations (Jodhpur, New Delhi, Nagpur and Kolkata). These stations represent the four 'prime' climates (arid, semi‐arid, sub‐humid and humid) over the Indian sub‐tropics. The models have been validated with the longer time‐series (10 years) of independent datasets (1994–2003) of 4 'prime' climates as well as datasets from 16 stations using one‐year datasets (termed as secondary stations) of the Indian region. The monthly diffuse fraction estimates were also compared with seven globally existing models. The 'regional' model showed more accurate estimates than 'local' models over three (semi‐arid, sub‐humid and humid) of the four 'prime' climates. However, the different error statistics showed that the 'regional' model outperformed the globally existing models which failed to capture diffuse fraction variability over the Indian sub‐tropics. The extendibility of the 'regional' model over 'secondary' stations in India showed an overall good performance with R2: 0.78–0.96 and RMSE: 0.017–0.125, except for two stations. These models are unique for Indian sub‐tropics and can undoubtedly be used for predicting future diffuse solar radiation fraction from transmissivity datasets of climate simulations, and also for other meteorological, climatological, solar energy‐based applications. Copyright © 2011 Royal Meteorological Society